2018
DOI: 10.1016/j.healun.2017.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of left ventricular dysfunction on utilization of donor hearts

Abstract: Roughly 20% of potential cardiac donors are excluded due to LVD. This figure has not been impacted by recent studies indicating that these hearts may be used safely. More complete data are required to understand why 11.04% of hearts that met inclusion criteria were refused for "poor function" without documented evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…11,12 Despite some previous articles dealing with the outcome of marginal heart donors with impaired LV function, the principle controversy remains in the field of heart transplantation. In particular, as most of past studies were based on the organ network database, [13][14][15][16] individual centers follow regimen regarding acceptance of marginal organs. However, in the setting of large retrospective register studies that include a heterogenous set of various wide-ranged perioperative protocols from a large number of institutions, the individual setting for the obtained data is not uniform.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Despite some previous articles dealing with the outcome of marginal heart donors with impaired LV function, the principle controversy remains in the field of heart transplantation. In particular, as most of past studies were based on the organ network database, [13][14][15][16] individual centers follow regimen regarding acceptance of marginal organs. However, in the setting of large retrospective register studies that include a heterogenous set of various wide-ranged perioperative protocols from a large number of institutions, the individual setting for the obtained data is not uniform.…”
Section: Introductionmentioning
confidence: 99%
“…4 Left ventricular (LV) dysfunction may be the single largest potentially modifiable factor preventing hearts from being transplanted from otherwise eligible brain-dead organ donors. 5 A significant proportion of young donors may have reversible impairments in LV function that could improve over time after sympathetic-mediated injury. 6 However, time for donor management and organ allocation is often limited by competing factors and therefore not all hearts that might recover are utilized.…”
Section: Introductionmentioning
confidence: 99%
“…In donors assessed for cardiac transplantation, LV dysfunction is cited as one of the most common contraindications for organ procurement, with one study finding this to be the case in up to 19% of non-utilized hearts. 14,15 A recent study showed that, although hearts with LV dysfunction as determined by preprocurement echocardiography were often declined, the presence of LV dysfunction in donor organs had no significant impact on post-transplant outcomes. 16 An NEVP system that allows for assessment of organ function and recovery postprocurement could potentially increase donor pool with organs that would have previously been declined.…”
Section: Discussionmentioning
confidence: 99%